The Effect of U.S. Climate Policy on Financial Markets: An Event Study of the Inflation Reduction Act - Michael D. Bauer; Eric A. Offner; Glenn D. Rudebusch (Center for Economic Studies and ifo Institute (CESifo), 2023)
The Inflation Reduction Act of 2022 (IRA) represents the largest climate policy action ever undertaken in the United States. Its legislative path was marked by two abrupt shifts as the likelihood of climate policy action fell to near zero and then rose to near certainty. We investigate equity price reactions to these two events, which represent major realizations of climate policy transition risk. Our results highlight the heterogeneous nature of climate policy risk exposure. We find sizable reactions that differ by industry as well as across firm-level measures of greenness such as environmental scores and emission intensities. While the financial market response to the IRA was economically significant, it did not lead to instability or financial stress, suggesting that transition risks posed by climate policies even as ambitious as the IRA may be manageable.
Keywords: G14; G38; Q54; Q58; 330; transition risk; stranded assets; event study; carbon emissions; ESG scores; green stocks; brown stocks